Outcome and recovery in first-episode psychosis. (December 2017) - Power, Paddy
Summary: There is now a good body of evidence about factors that determine outcome and recovery in a first episode of psychosis. However, so far, this is of limited benefit when making predictions at an individual level. Treatment protocols are one size fits all and the recommended duration of medication remains unclear. What is needed is a more sophisticated approach to predicting outcomes and tailoring treatment options to the individual. Removing predisposing factors is an important aspect of this.